Are Translators Traitors? A Philosophical Perspective of Loss and Gain in Translation (Global Journal of Human-Social Science, 2015)
Translators act as a key bridge that enables cross-cultural communication more so in multilingual contexts as is the case in Kenya. Among the challenges facing the process of translation is the rendering of meanings conceived in the source text as closely as possible in the translated text. This process is complex and has made some scholars to regard translation as an impossible exploit since it can never be totally equivalent to the original. Translators have been labeled "traitors" since even the best of their efforts can never bring out the intended meaning in the original text as was conceptualized by the author. This paper seeks to provide a philosophical understanding on the aspect of loss and gain in translation. It seeks to underpin the complexity of the "word" and hence the meaning rendered by these words. Using Nord's conceptualization of translation as a purposeful activity, we seek to analyze functionally the translation of "The Beasts of England" in Animal Farm from English to Kiswahili -Shamba la Wanyama.
Keywords: translation; loss; gain; meaning